2013
DOI: 10.1016/j.jss.2012.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Improving logic-based testing

Abstract: Logic-based testers design tests from logical expressions that appear in software artifacts such as source code, design models, and requirements specifications. This paper presents three improvements to logic-based test design. First, in the context of mutation testing, we present fault hierarchies for the six relational operators. Applying the ROR mutation operator causes each relational operator to generate seven mutants per clause. The fault hierarchies show that only three of these seven mutants are needed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 34 publications
0
56
0
Order By: Relevance
“…Kaminski et al [12] investigated a do-fewer approach. The relational operator replacement mutation operator (ROR) creates seven mutants per relational operator.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Kaminski et al [12] investigated a do-fewer approach. The relational operator replacement mutation operator (ROR) creates seven mutants per relational operator.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Kaminski et al investigated a do-fewer approach theoretically [20]. The relational operator replacement mutation operator (ROR) generates seven mutants for every relational operator in a program.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Offutt et al [35] found that focusing on replacing primitive operators sufficed to efficiently implement mutation testing for these languages. When implementing some of these operators, we can opt for (1) generating all possible mutations per mutation location, (2) producing a sufficient set of non-redundant mutations [36,37] or (3) introducing just one mutation in order to further reduce the cost. MuCPP implements option (1) for most of its operators, except for ARB, ROR, LOR and ASR, in which option (3) is implemented.…”
Section: Methodsmentioning
confidence: 99%